Contesting 'xenophobia' through civic education: explorations with ARESTA in Khayelitsha - Kraak, Shaun (Department of Sociology, 2017)
This thesis suggests that out of the work of ARESTA, a new notion of citizenship and belonging was developed, as a result of their workshops. This notion is furthermore articulated in various communities. In this notion, citizenship is no longer linked to indigeneity, but rather escaping war and hardship, the need to work, and place of work. It is further justified by the concept of Pan-Africanism and a common humanity. Contradictions in the findings of the thesis point to the limitations of this workshop and the importance of broader societal issues. This thesis concludes that ARESTA's intervention makes a significant contribution in opposing xenophobia, in the light of what is possible in South Africa today. However, its work is ameliorative rather than radical structural change, what may be needed is far more elusive at present.